Is celebrity news, news?. (February 2014) - Turner, Graeme
In asking if celebrity news really is news as we know it, this article turns to an examination of the modes of production characteristic of celebrity news. Celebrity news is highly dependent upon the services of the publicity and promotions industries, and upon the provision of visual material from an increasingly well-organized set of paparazzi agencies. With the importance of the visual in today's competitive media market, and the fact that most news organizations are now choosing to compete on the basis of entertainment rather than information, celebrity news has developed new modes of production that differentiate its practices and assumptions from many of the practices and assumptions underlying traditional versions of news and of newsgathering. Among the results, the article argues, is the redefinition of gossip as news, as it moves out of the social pages and onto the front pages.